Use of T-wave alternans in identifying patients with coronary artery disease. Issue 1 (January 2016) - Figliozzi, Stefano; Stazi, Alessandra; Pinnacchio, Gaetano; Laurito, Marianna; Parrinello, Rossella; Villano, Angelo; Russo, Giulio; Milo, Maria; Mollo, Roberto; Lanza, Gaetano A.; Crea, Filippo
Abstract : Aims: Microvolt T-wave alternans (MTWA) has been found to predict fatal events in patients with coronary artery disease (CAD). In a previous study, we found that MTWA values are higher in patients with CAD, compared with apparently healthy individuals. In this study, we assessed the relation between CAD and MTWA in patients with a diagnosis based on coronary angiography results. Methods: We studied 98 consecutive patients undergoing coronary angiography for suspected CAD. All patients underwent a maximal exercise stress test (EST), and MTWA was measured in the precordial ECG leads. Patients were divided into three groups: 40 patients without any significant (>50%) stenosis (group 1); 47 patients with significant stenosis (group 2); and 11 patients with a previous percutaneous coronary intervention (PCI) who had no evidence of restenosis (group 3). EST was repeated after 1 month in 24 group 2 patients who underwent PCI and in 17 group 1 patients. Results: MTWA was significantly higher in group 2 (58.7 ± 24 μV) compared with group 1 (34.2 ± 15 μV, P  < 0.01) and group 3 (43.2 ± 24 μV, P  < 0.05). An MTWA greater than 60 μV had 95% specificity and 82% positive predictive value for obstructive CAD. At 1-month follow-up, MTWA decreased significantly in patients treated with PCI (from 61.3 ± 22 to 43.5 ± 17 μV; P  < 0.001), but not in group 1 patients (from 50.5 ± 22 to 44.3 ± 19 μV, P  = 0.19). Conclusion: MTWA is increased in patients with obstructive CAD and is reduced by coronary revascularization. An assessment of MTWA can be helpful in identifying which patients with suspected CAD are likely to show obstructive CAD on angiography.